Microglial re-modeling contributes to recovery from ischemic injury of rat brain: A study using a cytokine mixture containing granulocyte-macrophage colony-stimulating factor and interleukin-3 - Matsumoto, Shirabe; Choudhury, Mohammed E.; Takeda, Haruna; Sato, Arisa; Kihara, Nanako; Mikami, Kanta; Inoue, Akihiro; Yano, Hajime; Watanabe, Hideaki; Kumon, Yoshiaki; Kunieda, Takeharu; Tanaka, Junya (Frontiers in Neuroscience, 2022)
Ischemic stroke is a leading cause of mortality and permanent disability. Chronic stroke lesions increase gradually due to the secondary neuroinflammation that occurs following acute ischemic neuronal degeneration. In this study, the ameliorating effect of a cytokine mixture consisting of granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-3 was evaluated on ischemic brain injury using a rat stroke model prepared by transient middle cerebral artery occlusion (tMCAO). The mixture reduced infarct volume and ameliorated ischemia-induced motor and cognitive dysfunctions. Sorted microglia cells from the ischemic hemisphere of rats administered the mixture showed reduced mRNA expression of tumor necrosis factor (TNF)-α and IL-1β at 3 days post-reperfusion. On flow cytometric analysis, the expression of CD86, a marker of pro-inflammatory type microglia, was suppressed, and the expression of CD163, a marker of tissue-repairing type microglia, was increased by the cytokine treatment. Immunoblotting and immunohistochemistry data showed that the cytokines increased the expression of the anti-apoptotic protein Bcl-xL in neurons in the ischemic lesion. Thus, the present study demonstrated that cytokine treatment markedly suppressed neurodegeneration during the chronic phase in the rat stroke model. The neuroprotective effects may be mediated by phenotypic changes of microglia that presumably lead to increased expression of Bcl-xL in ischemic lesions, while enhancing neuronal survival.